Two-span continuous bridge damage localization method based on vertical support reaction - Wang, Yi-lin (2014)
To localize the damage to main beams of continuous bridges accurately, a novel damage localization index based on the idea of "second order difference of support reaction influence line" was presented by employing influence line analysis for two-span continuous bridges. This index was called "difference index of influence line for vertical support reaction" (DⅡLSR). Subsequently, the damage localization method based on DⅡLSR was established. The results show that damage position of main beams with uncertain local flexural stiffness can be effectively identified by comparing two DⅡLSR graphs before and after damage. The effect of damage localization can be adjusted by changing the load value and the length of virtual interval.